The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4274/jcrpe.1003
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin and hsCRP Levels and Non-Invasive Radiological Methods in the Early Diagnosis of Cardiovascular System Complications in Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Objective: Adiponectin and high-sensitivity C-reactive protein (hsCRP) can be used as early biochemical markers of cardiovascular diseases (CVDs). Radiologically, non-invasive flow-mediated dilation (FMD) of the brachial artery and carotid intima-media thickness (CIMT) measurements may be used as indicators in the early diagnosis of CVDs. To compare the biochemical markers of atherosclerosis with radiological markers of CVDs (CIMT, FMD, ventricular systolic and diastolic functions) and to assess the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…These changes reflect early changes in myocardial relaxation. DD in diabetic children was reported by other investigators 21)22)23). LV DD in patients with diabets mellitus (DM) may be caused by increased LV diastolic stiffness, deposition of advanced glycation end (AGE) products, and cardiac fibrosis, all as a consequence of DM 3).…”
Section: Discussionmentioning
confidence: 83%
“…These changes reflect early changes in myocardial relaxation. DD in diabetic children was reported by other investigators 21)22)23). LV DD in patients with diabets mellitus (DM) may be caused by increased LV diastolic stiffness, deposition of advanced glycation end (AGE) products, and cardiac fibrosis, all as a consequence of DM 3).…”
Section: Discussionmentioning
confidence: 83%
“…It is normally present in plasma concentrations of 2–20 μg/mL 43. Most studies comparing adiponectin concentration in obese adolescents with its concentration in healthy controls referred to “low levels” when adiponectin concentration was <5 μg/mL, as compared with its concentration in healthy control subjects at >10 μg/mL 4446. Therefore, in the present study, we used the same cutoff points.…”
Section: Methodsmentioning
confidence: 99%
“…High sensitivity C-reactive protein (CRP) is the most studied inflammatory marker in pediatric type 1 diabetes. In healthy adults, CRP levels predict future cardiovascular disease and are linked to endothelial dysfunction [1315], Most [6, 7, 1622], but not all studies [23, 24], have demonstrated significant increases in CRP levels in pediatric T1D patients. Soluble intracellular adhesion molecule 1 (sICAM 1) is biochemical marker of endothelial damage and inflammation and is again elevated in pediatric T1D [7, 20, 2527].…”
Section: Introductionmentioning
confidence: 99%